Effect of extraction methods on food and biodiesel properties of shea-nut oil (Vitellaria paradoxa) - Audu, J; Awulu , J O (Journal of Postharvest Technology, 2016)
Shear nut oil is one of the most abundantly available vegetable oils produced in the sub Sahara region. It is mostly used for food and medicine. The need to use it for biodiesel to solve the energy need of the region has been a major concern for African. Three extraction methods, namely: Traditional, solvent and mechanical method was used to extract shear nut oil. Some food and biodiesel properties of the oil were tested and compared between each other. Properties investigated were; colour, moisture content, protein, free fatty acid, saponification, solidification, viscosity, melting point, specific gravity, flash point, cloud point, refractive index, iodine value. The results showed that extracting methods of Shea nut oil have a significant effect (p<0.05) on moisture content, protein, free fatty acid, saponification, viscosity, melting point and iodine but not on solidification, specific gravity, flash point, cloud point and refractive index. Among the three extraction methods compared, mechanical method had less effect on food and bio-diesel properties of shear nut oil, followed by the traditional method and then the solvent method.